Improving the thermal and hydrophobic properties of bamboo biocomposite as sustainable acoustic absorbers - Hassan Irvani; Hassan Asilian Mahabadi; Ali Khavanin; Ali Safari Variani (Scientific Reports)
Abstract The purpose of this research is to investigate the potential of chemical modification to improve the hydrophobic properties and thermal stability of bamboo fibers and to evaluate the sound absorption performance of raw and modified fibers. To achieve this goal, bamboo fibers were modified using stearic acid coatings and aluminum hydroxide nanoparticles. The results showed that the modification of fibers with stearic acid (STA) can improve the contact angle and hydrophobicity of bamboo fibers, so that for modified fibers with a concentration of 0.3 M, the contact angle was 143.8 degrees, placing the fibers in the superhydrophobic range.Additionally, the thermogravimetric results showed that aluminum hydroxide (ATH) loading increased the coal residue at 600 °C by 12%, indicating an improvement in hydrophobic properties and thermal stability. The average sound absorption for composites based on raw fiber and modified with STA and ATH in the range of 630–6300 Hz was 0.51 and 0.472, respectively. This shows that chemical modification has reduced the sound absorption of the composite to a small extent. On the other hand, the average sound absorption coefficient for frequencies above 630 Hz was 0.84 and 0.79, respectively, indicating that the sound absorption composite has good absorption. Overall, these observations provide strong evidence that chemical modification of natural fibers can lead to the development of more stable and safer porous acoustic absorbers.